Interpreting Cohort Profiles of Life Cycle Earnings Volatility - Blundell, Richard; Bollinger, Christopher R.; Hokayem, Charles; Ziliak, James P. (Journal of Labor Economics, 2025)
We present new estimates of earnings volatility over time and the life cycle for men and women by race and human capital, using Social Security earnings linked to the Current Population Survey. From the late 1970s to the mid-1990s, there is a strong negative trend in earnings volatility driven by a decline in transitory variance. From the mid-1990s, there is relative stability in trends of male earnings volatility due to an increase in the variance of permanent shocks. Cohort analyses indicate that earnings volatility is U-shaped, driven by large permanent shocks early and later in the life cycle.